Kesenjangan Digital dan Solusi yang Diterapkan di Indonesia Selama Pandemi COVID-19 - Ria Jayanthi; Anggini Dinaseviani (BPSDMP KOMNFO Yogyakarta, Kementerian Komunikasi dan Informatika, 2022)
The digital divide is a crucial issue in developing countries. Indonesia needs to find elite solutions to solve the issue. By looking at the speedy development of telecommunications and the cheapening of information technology, especially the internet, the expectation is to lower the digital gap problems. Bythis time, the digital divide discourse is mostly associated with the availability of access and infrastructure, even though good digital capabilities are a prerequisite for digital equality. This study aims to observe how the conditions of the digital divide in Indonesia and the way to solve it are presented by the government or individuals to overcome the digital divide. Using the descriptive qualitative method in this research is to illustrate the restrictions of the digital divide between provinces and regions in Indonesia and what solutions have been taken to address the digital divide in Indonesia. This study concludes that the enlargement of internet access in Indonesia has not been linear with the digital competency of its people. It includes motivation to be more productive using the internet, get useful information and use it for productive activities that can improve the economy.